2020
DOI: 10.3390/cells9122632
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes, Systemic Inflammation and Immunopathology in Acute-on-Chronic Liver Failure

Abstract: Acute-on-chronic liver failure (ACLF) is a complex syndrome that develops in patients with cirrhosis and is characterized by acute decompensation, organ failure(s) and high short-term mortality. ACLF frequently occurs in close temporal relationship to a precipitating event, such as acute alcoholic, drug-induced or viral hepatitis or bacterial infection and, in cases without precipitating events, probably related to intestinal translocation of bacterial products. Dysbalanced immune function is central to its pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 116 publications
(172 reference statements)
0
62
1
4
Order By: Relevance
“…Albumin was taken up by leukocytes and localized in endosomes, where it inhibited Toll-like receptor signaling. In patients with acutely decompensated cirrhosis, albumin administration has been shown to reduce inflammation, and may therefore involve a direct effect of albumin on leukocytes [ 44 ].…”
Section: Bio-mechanistic Relationship Between Hypoalbuminemia and Infectionmentioning
confidence: 99%
“…Albumin was taken up by leukocytes and localized in endosomes, where it inhibited Toll-like receptor signaling. In patients with acutely decompensated cirrhosis, albumin administration has been shown to reduce inflammation, and may therefore involve a direct effect of albumin on leukocytes [ 44 ].…”
Section: Bio-mechanistic Relationship Between Hypoalbuminemia and Infectionmentioning
confidence: 99%
“…Under normal conditions, viable bacteria are killed by the immune system, and their components are released into the systemic circulation, leading to systemic inflammation without overt bacterial presence. During LT, using high-dose hormones and immunosuppressants to suppress immunity permits the translocation of intestinal bacteria, leading to bacterial infection and sepsis [36]. In addition, patients with organ failure have more severe systemic inflammation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Mireia Casulleras group reported that a systemic hyperin ammatory state is the main driver of widespread tissue and organ injury in patients with ACLF. The massive release of in ammatory mediators leads to severe tissue damage [22].Jiang Li [23] group con rmed that HBV exacerbate immune-metabolism disorder in HBV-ACLF patients. Therefore, we thought that although received 12 weeks antiviral therapy making HBV DNA load decrease to lower level, immune and metabolic disorder process still drive the development and progression of HBV-ACLF in the followed time, which was the reason of why these two groups achieved similar survival rate after 12 weeks treatment.…”
Section: Discussionmentioning
confidence: 99%